Digital Photography in Public Spaces as an Emerging Challenge to Indonesia’s Privacy Protection and Information Ethics - Amelia, Dean Putri; Nurhasanah, Hikmah; Islami, Diajeng Dhea Annisa Aura; Tetrya, Selvi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes how the practice of digital photography in public spaces poses new challenges to privacy protection and information ethics in Indonesia. Advances in photography technology and the dissemination of visuals through digital platforms have encouraged people to spontaneously produce and distribute images, exposing individuals as subjects of photographs to the risk of privacy violations, especially when photographs are taken without consent. This study uses a normative juridical method that examines the provisions in the Personal Data Protection Law and the Electronic Information and Transaction Law to assess the legal boundaries related to the processing of individual portraits. The results of the study show that portraits and visual identities of individuals are categorized as personal data that must be protected, so that the act of taking, using, or commercializing photos without permission can have legal and ethical consequences. In addition, the practice of taking photos in public spaces, such as during Car Free Day activities, illustrates a change in the meaning of public space, which has now been transformed into a space for the production of visual data that is difficult to control. This phenomenon has created tension between freedom of expression and the protection of dignity, security, and personal integrity. This study confirms that harmonizing the right to freedom of expression and the principle of personal data protection requires a more adaptive regulatory and cultural approach, especially in the face of a rapidly changing and competitive digital ecosystem. Thus, efforts to improve digital literacy, photography ethics, and legal compliance are essential prerequisites for creating a safe, civilized digital public space that respects the rights of every individual.